The Implementation of Authentic Assessment in Speaking Tests for Secondary School Students - Leady Karisma Putri Lestari; Fithriyah Rahmawati; Indah Amelia; Nita Aprilia Utami; Rini Handayani (Penerbit STKIP PGRI Bangkalan, 2025)
The use of authentic assessment in speaking tests has gained greater significance to close the gap between theory and practice in the classroom. Although its value in measuring actual language skills in everyday life is well understood, its effective implementation by teachers remains a challenge, and inconsistencies in measuring students' speaking skills are the result. This study aims to explore the implementation of authentic assessment in speaking tests in SMA Negeri 5 Pamekasan, namely the implementation processes employed by teachers and the impact on the students' actual speaking abilities. Conducting a qualitative descriptive study, data were collected using interviews, observation, and documents to represent the naturalistic nature of the classroom and the teachers' assessment strategies. The study reveals that SMA Negeri 5 Pamekasan teachers have informal and formative tests that involve reading aloud, pronunciation, intonation, and confidence measures in classroom interactions. Question-answer and reading aloud are some of the strategies used to overcome the students' shyness to speak and judge their communications more realistically. The study concludes that authentic assessment, when properly understood and implemented, accurately measures students' speaking skills under actual circumstances and helps teachers understand how to direct further improvement. This study provides implications and pedagogical suggestions for teachers to enhance authentic assessment practice in English-speaking courses.